METACOGNITIVE ANALYSIS OF ELEMENTARY SCHOOL STUDENTS - Ari Metalin Ika Puspita (Indonesian Journal of Elementary Teachers Education, 2020)
This study aims was to investigate the metacognitive abilities of elementary school students. The subjects of this study were elementary school students and teachers from two districts namely Tulungagung and Trenggalek Regencies who had diverse scientific abilities. The data were collected through a questionnaires, semi-structured interviews, and documentation. The data were analyzed through several steps: data collection, data refinement, data processing, data analysis, data analysis process, and conclusions of research results. The results of the study are the aspects of strategic knowledge that is the problems found in schools based on learning strategies that are often done by students, namely repetition. In the aspect of task knowledge it was found that students did not use the right learning strategies with the assignments given by the teacher. While the students' self-knowledge, students have different characteristics. There are students who excel in the academic and non-academic fields. So that each student has advantages and disadvantages both mastery of learning material and outside of learning. This causes differences in achievement for each student.Keywords: elementary school students; metacognitive.